Use of coral rubble, aquamat and aquaponic biofiltration in the recirculating system of a marine fish hatchery - Abentin Estim; Saleem Mustafa (Virginia Tech, Blacksburg, VA USA, 2011)
A preliminary study on the effect of combination biofilters, including coral rubble, geotextile AquamatTM (Meridian Aquatic Technology, Silver Spring, MD, USA), and algal aquaponics in a marine fish recirculating system was investigated. AquamatTM is an innovative product fabricated from highly specialized synthetic polymer substrates. AquamatTM forms a complex three-dimensional structure that resembles seagrass in appearance, and has been used to support high stocking densities in fish culture ponds and enhance biological processes. In addition, coral rubble was used, and two seaweed species, Eucheuma spinosum and E. cottonii, were evaluated for their usefulness as aquaponic biofilters in a recirculating system. Results showed that the four different biofilters operating within the recirculating system were significantly different (P<0.05) in NH3-N and NO3-N concentrations. The lowest mean NH3-N concentration was recorded in the recirculating tank using AquamatTM + seaweed + coral rubble, while the highest mean NO3-N concentration was recorded in the recirculating tank using AquamatTM + coral rubble. Fish weight gain and survival rates were not significantly different (p<0.05) in the four recirculating systems. In the second experiment, three varieties of Eucheuma spp. grew poorly, and produced no noticeable effects on NH3-N, NO2-N and NO3-N concentrations. Eucheuma cottonii decayed in the early days, while the two varieties of E. spinosum decayed after 35 days. Once decayed, water quality impairment followed This study concluded that Eucheuma species were not suitable as a method of biofiltration in a recirculating culture system. While these seaweeds do remediate water quality, they themselves require a good environment to perform this role. When conditions are not optimal for the stocked organisms, the co-culture system can produce negative results. Follow-up investigation is needed to determine the suitability of such integrated aquatic systems for a large-scale fish production in recirculation systems